2009
DOI: 10.1007/s00228-009-0687-7
|View full text |Cite
|
Sign up to set email alerts
|

Children’s presence in research. A review of online registers

Abstract: Objectives To determine how many online clinical trial registers include paediatric trial data, how much information is provided, ease of searching for paediatric trials and the accessibility of paediatric trial data in general. Methods Medline and Google were searched for mention of clinical trial registers in July 2008. All registers considered to be eligible were evaluated for trial information provided, search options available, and number of trials, both total and paediatric. A meta-analytic weighted aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, trial registration is far from universal, and is perhaps more problematic in pediatric trials. Pandolfini and Bonati [29] found that the proportion of pediatric trials among all registered trials in online registers was disproportionate to those in the published literature. Pediatric trials are more likely to be published in specialty journals which may be less likely to require trial registration than general medical journals.…”
Section: Discussionmentioning
confidence: 99%
“…However, trial registration is far from universal, and is perhaps more problematic in pediatric trials. Pandolfini and Bonati [29] found that the proportion of pediatric trials among all registered trials in online registers was disproportionate to those in the published literature. Pediatric trials are more likely to be published in specialty journals which may be less likely to require trial registration than general medical journals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work analysing the rate of registration of pediatric trials suggests that authors of pediatric trials have been slow to prospectively register their studies, despite the fact that many journals stipulate that prospective registration is a prerequisite for publication[28], [29]. Therefore it seems likely that analysing the number of registered trials would substantially underestimate the number of trials actually being conducted.…”
Section: Discussionmentioning
confidence: 99%